Analisis Pengaruh Penambahan Jam Kerja Terhadap Durasi Waktu Penyelesaian Proyek Konstruksi Jalan - Cicilia, Briney; Puspasari, Veronika Happy; Dewantoro, Dewantoro (Program Studi Teknik Sipil Fakultas Teknik Universitas Palangka Raya, 2025)
The completion time and cost accuracy of a project can be evaluated based on the achievement of quality standards and timely delivery. Thorogh planning and scheduling are essential to ensure that the project is completed within budget and on time. This study is a case study conducted on the road improvement project of the turan amis – malintut section in East Barito regency, central Kalimantan, with a project duration of 150 days, starting from June 24, 2022, to November 20, 2022. The aim of this research is to analyze the project task that underwent acceleration using the crashing metod and to evaluate the reduction of project duration through extended working hours. The data used in this study include the time schedule and budget plan, wich were obtained from the project implementers. The data analysis technique used is CPM, with the crashing method applied using Microsoft Project and Microsoft Excel. The result show that extending working hours by 1 hour reduced the project duration to 138 days, while 2 hours extension short the duration to 130 days, resulting in a 14% time efficiency. Considering the time efficiency, the alternative of adding 2 working hours was selected to accelerate the project completion.